Measurement of Information System Project Success Based on Perceptions of the Internal Stakeholders - A'ang Subiyakto; Abd. Rahman Ahlan; Mira Kartiwi; Husni Teja Sukmana (International Journal of Electrical and Computer Engineering (IJECE), 2015)
In this research, adoption of the DeLone and McLean (D&M) information system (IS) success model and its adaptation with the project success theories were used to explore state of IS project success and to examine factors which affect its success. A survey towards the internal project stakeholder in an univerity with response rate 48% was carried out to collect the raw data for Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. Majority of the participants (80.7%) stated that level of the project success is more than 50% where information quality, system quality, service quality, system use, and user satisfaction substantially explain 64.5% of variance in the success variable. The three quality factors together explain 43.2% of the variance of system use and 70.4% of the variance of user satisfaction. Although, a number of the findings were consistent with the prior studies, these findings also presented inconsistencies especially related to aspects of information quality and system use. Accordingly, researchers and practitioners will be stand to benefit from the information provided in this study and it is hoped that future research will build upon the findings reported herein as efforts are made to attain the IS project success especially in the sampled institution.